Readiness assessment for knowledge management : a case of the civil service college. - Soong, Corrinne Heng Yue. (2008)
In view of the need to review the readiness of a public sector organization in Singapore for knowledge management, this study was conducted to ascertain the preparedness of the organization in the Technology, Business and Cultural environments. The research methodology used in this study is a questionnaire survey modeled after Jan Duffy’s Knowledge Management Readiness Assessment Checklist. The questionnaire survey was administered to 92 staff, out of which 85 returns were valid. Following the feedback collected, some informal discussion sessions with selected respondents were conducted to verifj the researcher’s interpretation of the results.